(untitled) (JOSAR (Journal of Students Academic Research), 2021)
This study aims to analyze the meaning of the song Fiersa Besari according to the Greenhouse Effect. Fiersa Besari’s “Celengan Rindu” has a historical meaning to reveal the problem of long-distance dating as a barrier to meeting a lover. In addition, there are expressions of hope and expressions of various wishes to meet each other and carry out joint activities. In a dialectical meaning, the text of this song has meaning, expressing rejection of one’s barriers in long distance relationships. In terms of researchers’ prejudice, this song means that long distance courtship limits longing and limits communication. However, face-to-face encounters between two individuals who have been dating long-distance is a long-awaited time to spend together. Then finally, the researchers captured the linguistic meaning of the word. The connotative of the assonance language style is the repetition of the phrase "and wait for me there to break my longing piggy bank" the total effect of the nuances is the feeling of missing Fiersa Besari for her lover and her desire for her lover is waiting for him to come to her.